Pengelolaan Zakat, Infaq dan Sedekah dalam Pengembangan Usaha Mikro di Baznas Gresik - Mariroh, Silvi Mata'atul; Anwar, Moch Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2020)
Poverty illustrates a multidimensional problem on economic factors, the emergence of programs implemented by the government to reduce the number of poor people such as distributing cash donations. Therefore the plan to make it happen Gresik Regency Baznas prepares a work program that is "Micro Finance Program" which is a program of assistance for small businesses with the aim of developing their businesses so they can develop and be able to return them to the mustahik in need. This research is a qualitative research that intends to look at the management model of zakat, infaq, and alms in developing micro businesses. From the results of the study it can be concluded that the management model of zakat, infaq, alms in the development of micro businesses in Baznas Gresik Regency is a Gresik empowered program where productive economies are held in microbusiness groups. Overall the achievement of the ZIS management program at the Gresik Regency Baznas has been optimal.